A multicenter phase II randomized trial of durvalumab (MEDI-4736) versus physician's choice chemotherapy in recurrent ovarian clear cell adenocarcinoma (MOCCA). Issue 8 (25th June 2020) - Ngoi, Natalie YL; Heong, Valerie; Ow, Samuel; Chay, Wen Yee; Kim, Hee Seung; Choi, Chel Hun; Goss, Geraldine; Goh, Jeffrey C; Tai, Bee Choo; Lim, Diana GZ; Kaliaperumal, Nivashini; Au, Veonice B; et al.
Abstract : Background: The optimal treatment of recurrent ovarian clear cell carcinoma remains unknown. There is increasing rationale to support the role of immune checkpoint inhibitors targeting the programmed cell death protein 1 (PD - 1)/programmed death-ligand 1 (PD-L1) axis in ovarian clear cell carcinoma. Primary objective: To evaluate the efficacy of durvalumab (MEDI-4736) compared with standard chemotherapy in patients with recurrent ovarian clear cell carcinoma. Study hypothesis: Patients with recurrent ovarian clear cell carcinoma treated with durvalumab will have improved progression-free survival compared with those treated with chemotherapy of physician's choice. Trial design: The MOCCA study is a multicenter, open-label, randomized phase II trial in patients with recurrent ovarian clear cell carcinoma, which recruited from eight sites across Gynecologic Cancer Group Singapore (GCGS), Korean Gynecologic-Oncology Group (KGOG), and Australia New Zealand Gynecological Oncology Group (ANZGOG). Enrolled patients were randomized in a 2:1 ratio to receive durvalumab or physician's choice of chemotherapy until disease progression, intolerable toxicity, or withdrawal of patient consent. Major inclusion/exclusion criteria: Eligible patients required histologically documented diagnosis of recurrent ovarian clear cell carcinoma, as evidenced by WT1 negativity. All patients must have been of Eastern Cooperative Oncology Group (ECOG) performance status 2 or better, and have had previous treatment with, and progressed or recurred after prior platinum-based chemotherapy. No more than four prior lines of treatment were allowed and prior immune checkpoint inhibitor treatment was not permitted. Primary endpoints: The primary endpoint was the median progression-free survival following treatment with durvalumab, compared with physician's choice of chemotherapy. Progression-free survival was defined as the time from the first day of treatment to the first observation of disease progression, or death due to any cause, or last follow-up. Sample size: The target sample size was 46 patients. Estimated dates for completing accrual and presenting results: Accrual has been completed and results are expected to be presented by mid-2021. Trial registration: Clinicaltrials.gov: NCT03405454 .